Comparative Analysis of Generation Z’s Perceptions of Sustainable Careers in the Czech Republic and Finland - Šimurková, Miriama (My University, 2026)
Due to the constantly changing labour market, the importance of long-term, meaningful, and viable careers is growing. Questions regarding what makes a career sustainable have received more attention in academic research, but this attention has focused primarily on long-term career development and objective outcomes. There is little known about how young people at the beginning of their careers interpret career sustainability in their own words and how these meanings are shaped by the national context in which their careers are developing. This thesis addresses these questions by comparing two countries with different institutional back-grounds in the European Union, namely the Czech Republic and Finland. The aim is to examine how members of Generation Z interpret and define the concept of a sustainable career in the early stages of their professional lives and whether these interpretations reflect differing na-tional conditions in the labour market and welfare system. The sustainable career framework by De Vos et al. (2020), which conceptualises career sustainability as a dynamic balance be-tween health, happiness, and productivity across the dimensions of person, context, and time, serves as the primary theoretical foundation. National context is examined through Walther's (2006) typology of transitional regimes, positioning Finland as a universalist regime and the Czech Republic analytically closer to an employment-centred configuration. The empirical basis consists of twelve semi-structured individual interviews, six per country, conducted with higher-educated early-career participants meeting Generation Z membership criteria. Data were analysed using theory-informed thematic analysis following the procedure consisting of six phases described by Braun and Clarke (2006). The findings suggest that all three indicators of career sustainability were reflected in the participants’ perceptions, even though they lacked prior knowledge of this framework. The balance between meaningful work, psychologi-cal well-being, and professional growth represents how they perceive career sustainability. A key analytical finding is that individuals at the beginning of their careers were guided by the logic of temporary compromises and consciously accepted current stress and uncertainty as a time-limited investment in future career stability. The most pronounced cross-national differ-ences were observed in structural conditions. Whereas Czech participants operated in a more accessible labour market, Finnish participants faced greater challenges in the labour market despite stronger social support. Notably, the protective nature of the Finnish social security system did not translate into a less stressful career experience under current economic condi-tions. Considering that the study is based on twelve interviews with early-career participants with higher education, the findings offer an interpretive perspective on how a specific group of young individuals constructs the meaning of career sustainability, but not general conclusions about Generation Z as a whole.
Keywords: sustainable development; career development; labour market; Czech Republic; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business